Metal-catalyzed plastic depolymerization - Khopade, Kishor V.; Chikkali, Samir H.; Barsu, Nagaraju (Cell Reports Physical Science, 2023)
Polymers have become an indispensable part of our daily lives, and today we produce around 370 MT of plastic per year. Only about 20% of it is being recycled, and the rest, 80%, is unleashed into the environment without appropriate treatment. This calls forth the evaluation of strategies available for mitigating the menace of ``after-use''plastic waste. Various approaches have evolved over a decade and are at different levels of development. Plastic depolymerization and upcycling are considered some of the most prominent and long-term solutions. The metal-catalyzed depolymerization of plastic waste to chemical feedstocks has emerged as one of the promising ways to address global plastic pollution. Therefore, this review aims to examine the available metal-catalyzed depolymerization methods, notify recent progress, pinpoint current gaps, and gauge the potential of this strategy. Both homogeneous and heterogeneous catalysts have been reported to depolymerize various polymers over the last decade. Considerable advances have been reported in the metal-mediated depolymerization of polyolefins, polyesters, polycarbonates, polyurethanes, polyamides, and polyethers. The depolymerization of the above polymers produces the monomers or intermediates, which can be used again for polymerization and thus brings the waste polymers back into circularity. The overview debates the usage of high temperaagents, etc., in metal-catalyzed depolymerization. Thus, this review summarizes the current understanding of the fundamental science of metal-catalyzed plastic depolymerization, the remaining scientific challenges, and the potential opportunities.

Depolymerization of waste polyethylene to linear alkenes via sequential dehydrogenation and metathesis - Khopade, Kishor V.; Rajput, Nikhita S.; Rangappa, Raghavendrakumar; Barsu, Nagaraju; Chikkali, Samir H. (Green Chemistry, 2024)
Polyethylene (PE) is the most abundantly sourced plastic and significant efforts are needed for its end-of-life management. The deconstruction of PE is an uphill task and requires the breaking of highly stable C-C bonds. Here we demonstrate that PE can be deconstructed to value-added dodecene, along with other long-chain alkenes. The PCP-iridium complex catalyzes the dehydrogenation of commercial and post-consumer polyethylene waste to produce dehydrogenated polyethylene (DHP) with 0.5-1.0% unsaturation. The DHP was subjected to an ethylene cross-metathesis reaction in the presence of suitable catalysts. Through meticulous optimization of reaction parameters, 63% selectivity toward dodecene, with 26% overall yield, was achieved. The practical significance of our method has been demonstrated by subjecting post-consumer plastic waste to dehydrogenation followed by ethylene metathesis to produce dodecene as a major product, together with long-chain alkenes. The PE deconstruction has been confirmed by recording molar mass before and after depolymerization using high-temperature gel permeation chromatography. The existence of dodecene has been unambiguously ascertained using GC, GC-MS, NMR, and IR spectroscopy. Thus, these results demonstrate the conversion of waste PE to value-added dodecene and long-chain alkenes under mild reaction conditions.

Hybrid silylene-Pd catalyst: efficient C-N cross-coupling of sterically bulky amines and chiral amines - Kaulage, Sandeep H.; Parvin, Nasrina; Khopade, Kishor V.; Khan, Shabana (Chemical Communications, 2024)
Herein, we report a catalytic system with N-heterocyclic silylene (NHSi)-phosphine-based hybrid bidentate ligands [PhC(NtBu)2SiN(PR2)(2,6-iPr2-C6H3)] and Pd(dba)2, which serves as an effective catalyst for C-N cross-coupling of a wide range of sterically bulky amines and optically active amines, which is challenging otherwise. Herein, we report a hybrid silylene-based bidentate ligand (SiNP)-Pd(0) catalytic system, which performs the C-N coupling of difficult substrates, e.g., sterically bulky amines and chiral amines.

Portal substituent modulations in chiral imido-Pd(II) cages for the enhanced separation of styrene oxide enantiomers - Jose, Cavya; Sarkar, Abhradeep; Khopade, Kishor V.; Boomishankar, Ramamoorthy (Inorganic Chemistry, 2025)
Sensing and separation of enantiomers are crucial for the synthesis of biologically relevant compounds as well as for applications in catalysis and pharmaceutical development. Chiral coordination cages have gained significant attention as effective platforms for enantioselective processes through their well-defined, tunable cavities that facilitate host-guest interactions. In this study, we systematically explored the enantioselective binding and separation properties of two tetrahedral Pd(II) cages, 1-R and 2-R, with the molecular formula [Pd3(PO[N(RCH(CH3)Ph)3])4(C6O4X2)6] (X = Cl for 1-R, and X = F for 2-R). Their enantioselective abilities were investigated for small chiral molecules with diverse functional groups. Notably, the 2-R cage demonstrated a high enantioselectivity value of 88 for R-styrene oxide. Chiral separation experiments further revealed impressive enantiomeric excess (ee) values of 98% for R-styrene oxide from their racemic mixtures upon desorption from 2-R. The enhanced selectivity and separation efficiency were attributed to an optimal guest-to-cavity fit and the presence of multiple interaction sites within the host framework. Remarkably, portal substituent modulation in 2-R led to a 16-fold enhancement in enantioselective separation efficiency compared to 1-R, primarily due to improved portal dimensions, tighter molecular packing, and increased hydrogen bonding interactions. These findings highlight the potential of neutral chiral coordination cages for various enantioselective applications.

Rh-Catalyzed Asymmetric Hydroformylation: The Case of Substituted and Heterocyclic Olefins - Tewari, Tanuja; Khopade, Kishor V.; Chikkali, Samir H. (ChemCatChem, 2025)
Asymmetric hydroformylation (AHF) of prochiral alkenes is an efficient way to synthesize optically active aldehydes, which are versatile chiral building blocks for pharmaceuticals, agrochemicals, and other fine chemicals. The purpose of this review is to take stock of developments in the last decade and shed light on the understanding of the field of AHF. So far, most of the literature methods focused on the use of Rh-based catalysts, due to high catalytic activity and excellent chemoselectivity for the aldehydes. Several chiral phosphorus ligands have been successfully developed for Rh-catalyzed AHF reactions. This review examines the role of the substrate/olefins in AHF. Several different types of ``mono-substituted'' terminal olefins (functionalized/nonfunctionalized) with a variety of chiral ligands have been investigated, which show high activity and excellent ee of up to 99%. The AHF of ``di-substituted'' and ``tri-substituted'' olefins is rarely reported. This review summarizes the evolution of chiral ligands for AHF. It discusses the progress made in desymmetrizing hydroformylation. In addition, it highlights important developments in AHF carried out with and without syngas. These advances span a wide variety of alkenes. Additionally, the review offers future approaches in the field of AHF for the synthesis of optically active aldehydes.
Keywords: Asymmetric hydroformylation; Asymmetric transfer hydroformylation; Chiral ligands; Desymmetrizing hydroformylation; Substituted alkenes

Ruthenium-catalyzed deconstruction of polyolefins: a strategy to up-cycle waste polyethylene to value-added alkene - Padhi, Ganeshdev; Khopade, Kishor V.; Moyilla, Nageswararao; Rangappa, Raghavendrakumar; Chikkali, Samir H.; Barsu, Nagaraju (Angewandte Chemie-International Edition, 2025)
Synthesis of value-added products from post-consumer waste polyolefins is fascinating as well as challenging. Here we report ruthenium-catalyzed up-cycling of the polyethylene to long-chain alkene derivatives. The developed methodology mainly involves two steps i.e., dehydrogenation of polyethylene through hydrogen atom transfer and its metathesis using the HG-II catalyst. The dehydrogenation of polyethylene using ruthenium catalysis derived up to 3.38 %, of double bonds; with 90 % of the recovered polyolefin material. The obtained unsaturated polyethylene was subjected to cross-metathesis with ethylene using HG-II catalytic system. This resulted in the synthesis of predominantly dodecene (C12) derivatives, with 58 % selectivity, along with other derivatives of varying chain lengths. The overall reaction produced terminal and internal olefins in the ratio 1:0.8 respectively. The dehydrogenation of polyethylene and its deconstruction was confirmed by NMR spectroscopy, Gel Permeation Chromatography (GPC) and Differential Scanning Calorimetry (DSC). The origin of C12 selectivity has been demonstrated by control experiments. The scope of the methodology was extended to post-consumer waste polyethylene which gave high conversion to value-added dodecene derivatives as a major product.
Keywords: Deconstruction; Homogeneous catalysis; ruthenium; Upcycling; Waste plastic

Direct synthesis of phosphine-phosphite ligand and its implication in asymmetric hydrogenation of functionalized olefins - Chandanshive, Amol C.; Khopade, Kishor V.; Chikkali, Samir H. (Chemistryselect, 2026)
Phosphine-phosphite (P-OP) ligands constitute a privileged class of chiral ligands in asymmetric catalysis owing to their modular structures and tunable steric and electronic properties. Herein, we report a direct, one-pot, synthesis of a new flexible P-OP ligand (L) derived from BINOL-PCl and its in situ complexation with rhodium (Rh) for catalytic evaluation. The resulting Rh/L system efficiently hydrogenates a diverse library of 19 functionalized olefins under mild conditions, delivering moderate to excellent enantioselectivities, with ee values reaching up to 99%. Several of the hydrogenated products correspond to valuable chiral building blocks relevant to pharmaceutical synthesis, underscoring the practical utility of flexible P-OP ligand architectures in asymmetric hydrogenation.
Keywords: asymmetric hydrogenation; functionalized alkene; ligand design; metal catalyzed; phosphine-phosphite